PEMBINAAN ATLET UNGGULAN SEBAGAI REFLEKSI BUDAYA SUATU DAERAH: DEVELOPMENT OF EXCELLENT ATHLETES AS A CULTURAL REFLECTION OF A REGION - I Bagus Endrawan (Lembaga Pengembangan Kinerja Dosen, 2022)
The service is given to students, especially sports education, aims to teach students about an area's achievements and sports culture. This activity was carried out at the Educational Sciences Teacher College (STKIP) BIMA Taman Siswa, Health and Recreation Physical Education Study Program, which aims to motivate students, especially the Health and Recreation Physical Education study program to be able to develop the potential of cultural sports. In the region and pay attention to health aspects in development sports potential. The implementation method in this service activity is online through the Zoom Meeting application and offline counseling that discusses sports management, increasing achievements, and exploring the potential of an area's sports culture through the Zoom Meeting application. The result of this service activity is a program for coaching athletes who excel in improving performance as a reflection of the socio-cultural potential of sports in an area where there is a change in culture and the tendency of modern sports culture because it includes elements of knowledge, technology, and economic culture that are in line with the times. It is hoped that this will serve as a guide for long-term coaching programs to prepare excellent athletes who advance their respective regional sports cultures.